Bullying Victimisation Among Deaf Adolescents: A School-Based Self-Report Survey in Ghana. Issue 1 (2nd January 2022) - Fobi, Daniel; Quarshie, Emmanuel Nii-Boye; Fobi, Joyce; Appau, Obed; Honu-Mensah, Cyril Mawuli; Acheampong, Emmanuel Kwasi; Abu –Sadat, Rabbi
ABSTRACT: Regional and national level data on bullying victimisation and its associated factors among deaf adolescents are still lacking, particularly, in Africa. We conducted a cross-sectional self-report anonymous survey involving a nationally representative random sample of 450 school-going deaf adolescents in Ghana. Bivariate and multivariate analyses of the data showed the overall 12-month prevalence estimate of bullying victimisation to be 55 · 1% (95% confidence interval [CI]: 50% – 60%), but the estimates were comparable between females (52 · 0%) and males (57 · 0%). Whereas deaf adolescents with schoolwork problems were likely to report bullying victimisation, most of the key factors associated with bullying victimisation were adverse social events – break-up, conflict with friends, and parental divorce. These findings underscore the need for further studies, and school-based intervention and prevention efforts.